English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Simplify by combining like terms.

square root of 63 - 2 square root of 28 + 5 square root of 7

2006-10-27 12:44:01 · 5 answers · asked by Anonymous in Science & Mathematics Mathematics

5 answers

it is easiest to factor each of the numbers:
= √(63) - 2√(28) + 5√(7)
= √(3*3*7) - 2√(2*2*7) + 5√(7)

Now whenever you have a factor twice (e.g. √(3*3), this is the same as 3).

So,
√(3*3*7) = √(3*3) * √(7) = 3√(7)

Simplifying:
= 3 √7 - 4 * √7 + 5 * √7

Now factor out a common √7:
= (3 - 4 + 5) √7

So your final answer is:
= 4 √7

2006-10-27 12:46:44 · answer #1 · answered by Puzzling 7 · 1 0

Square root of 63 = square root of (7*9)= 3 square root 7
Square root of 28 = square root of (7*4)= 2 square root 7

So, here is what you will have:
3 square root of 7 - 2 square root of 7 + 5 square root of 7
As you see, the square roots are all the same, so you can add/subtract the constants
So you will have 3-2+5=6 square root of 7.

2006-10-27 19:50:51 · answer #2 · answered by danjlil_43515 4 · 0 0

√63 - 2√28 + 5√7

= 3√7 - 4√7 + 5√7

= (3 - 4 + 5)√7

= 4√7

*** The guy above copied the square root radical symbol (√) from my answer.

2006-10-27 19:48:44 · answer #3 · answered by عبد الله (ドラゴン) 5 · 1 1

square root of 63 - 2 square root of 28 + 5 square root of 7 =
(sqrt(7))(3 - 4 + 5) =
4sqrt(7)

Also
(3 - 4 - 5) = -6sqrt(7)
(3 + 4 + 5) = 12sqrt(7)
(3 + 4 - 5) = 2sqrt(7)
(-3 - 4 + 5) = -2sqrt(7)
(-3 - 4 - 5) = -12sqrt(7)
(-3 + 4 + 5) = 6sqrt(7)
(-3 + 4 - 5) = -4sqrt(7)

2006-10-27 19:53:06 · answer #4 · answered by Helmut 7 · 0 0

SQRT 63 = SQRT 9*7 = 3 SQRT 7
SQRT 28 = SQRT 4*7 = 2 SQRT 7
So now all are SQRT 7, so ;you can combine
(3 - 2*2 +5)SQRT 7 = 4 SQRT 7

2006-10-27 19:50:16 · answer #5 · answered by Steve A 7 · 0 0

fedest.com, questions and answers